Professional Oral Hygiene in The Complex of Therapeutic and Preventive Measures in Patients with Inflammatory Periodontal Diseases - Rakhmonova Feruza Mutalibovna (Scientific Trends, 2023)
The article presents data reflecting risk factors in inflammatory periodontal diseases, atherosclerosis, diabetes mellitus, and metabolic disorders. Periodontitis and these systemic diseases are considered through common pathogenetic mechanisms associated with systemic inflammation. Studies on bacteremia arising from the treatment of periodontitis are discussed, since episodic bacteremia is observed even with minimal trauma, including brushing the teeth, flossing, chewing, removing dental deposits. Treatment of periodontal diseases improves glycemic parameters and reduces the risk of cardiovascular complications.
Keywords: inflammation, periodontitis, atherosclerosis, diabetes mellitus, bacteremia.